Pedological inferences applied to Custódia irrigated perimeter, in Pernambuco State, Brazil - de Oliveira, Lindomário Barros; Ribeiro, Mateus Rosas; Ferreira, Maria da Graça de Vasconcelos Xavier; de Lima, José Fernando Wanderley Fernandes; Marques, Flávio Adriano (Pesquisa Agropecuaria Brasileira, 2002)
This work was carried out to evaluate the properties and the behavior of alluvial soils of the Custódia irrigated perimeter, in Pernambuco State, Brazil, whose agricultural use was interrupted due to salinity/sodicity problems. Morphologic, physics, chemistry and mineralogical characterizations of three profiles of affected soils for salts of the referred irrigated perimeter was used. The soils were classified, in agreement with the Brazilian System of Classification of Soils, as Solodic Eutric Fluvic Neosol, Saline Sodic Fluvic Neosol and Typic Sodic Fluvic Neosol. The stratification, what is typical in alluvial soils, governs the physical and chemical behavior of the soils studied in the vertical direction. In spite of the presence of minerals that can contribute to the process of salinization/sodification, such contribution should be minimum when compared to the low quality of irrigation water. The reutilization of these soils with irrigated agriculture should be preceded of liming and of an efficient drainage system that prevents water table rise and promotes the leaching of sodium.
Keywords: sodic soils; salinity; soil chemicophysical properties; soil morphological features; semi-arid